Continuous adoption of internet banking: evidence from Islamic banks in Malaysia - Mohd Thas Thaker, Hassanudin; Mohd Thas Thaker, Mohamed Asmy; Khaliq, Ahmad; Allah Pitchay, Anwar; Iqbal Hussain, Hafezali (2019)
Drawing on UTAUT2 framework, this study aims to investigate the behavioural intention and adoption of internet banking (IB) among clients of local and foreign Islamic banks in Malaysia, using Partial Least Squares analysis. Survey questionnaires were distributed among the Islamic bank's clients at two main places (i) Klang Valley and (ii) Selangor and primary data was collected from 319 clients. The SmartPLS analysis yielded three main outcomes: 1) the variables such as performance expectancy, effort expectancy, price value, facilitating conditions and habit have a positive influence over the behavioural intention and subsequently lead to the adoption of IB. The other two variables, namely social influence and hedonic motivation were negatively related and insignificant for behavioural intention. Thirdly, we also noticed that facilitating conditions and habit have a direct relationship with the adoption of IB. The implications of these outcomes are discussed from theoretical and practical perspectives.